Is There a Key Primer for Amplification of Core Land Plant DNA Barcode Regions (rbcL and matK)? - Leonardo C. J. Corvalán; Amanda A. deMelo‐Ximenes; Larissa R. Carvalho; Carlos de M. e Silva‐Neto; José A. F. Diniz‐Filho; Mariana P. de C. Telles; Rhewter Nunes (Ecology and Evolution)
ABSTRACT The DNA barcode is a technique for molecular identification of species. Two core genes, matK and rbcL, are widely used for land plants. In this technique, the selection of primers is a fundamental step for the success of amplification. Then, we aim to evaluate the primer amplification capability for the DNA barcode regions rbcL and matK. We extracted primer sequences from DNA barcode studies in the Web of Science and used chloroplast genome sequences from NCBI for in silico PCR tests using OpenprimeR. Physicochemical properties of in silico PCR were evaluated using OpenprimeR. Our literature review resulted in 366 and 489 different rbcL and matK primers. These were tested in 8665 sequences, 8463 species from 98 orders. Evaluating only the primer and sequence match, the primers with the highest number of sequences covered were 96.39% and 93.81% forward and reverse for rbcL, and 91.56% and 61.62% forward and reverse for matK. No universal primer for all land plants was found, but two rbcL primer pairs could amplify > 99% of the sequences. In contrast to the results obtained for the matK region, the 10 pairs optimized for the greatest coverage of sequences were not covered by > 85% of the sequences. Therefore, it is advisable to pay attention when selecting primers for the matK region and the need to develop new primers. Here, we recommend a set of primers to cover the largest number of sequences and orders.